2019
DOI: 10.1111/jace.16905
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of rotating lattice single‐crystal formation in Sb2S3 glass by Laue μXRD

Abstract: Single-crystal architectures in glass, formed by a solid-solid transformation via laser heating, are novel solids with a rotating lattice. To understand the process of lattice formation that proceeds via crystal growth, we have observed in situ Sb 2 S 3 crystal formation under X-ray irradiation with simultaneous Laue micro X-ray diffraction (μXRD) pattern collection. By translating the sample with respect to the beam, we form rotating lattice single (RLS) crystal lines with a consistently linear relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Au-Yeung et al demonstrated the possibility of crystallizing glass via X-ray beam heating while also acquiring Laue diffraction patterns in real-time. 96 The authors were able to recreate Sb 2 S 3 RLS crystals in stoichiometric glass via the alternative heat source with a very small 𝜅 21 of ∼0.07 • /μm. The real-time micro-X-ray diffraction attached to the fabrication of these particular crystals allowed scientific exploration well beyond just real-time lattice curvature quantification.…”
Section: X-ray Beam Heatingmentioning
confidence: 99%
See 3 more Smart Citations
“…Au-Yeung et al demonstrated the possibility of crystallizing glass via X-ray beam heating while also acquiring Laue diffraction patterns in real-time. 96 The authors were able to recreate Sb 2 S 3 RLS crystals in stoichiometric glass via the alternative heat source with a very small 𝜅 21 of ∼0.07 • /μm. The real-time micro-X-ray diffraction attached to the fabrication of these particular crystals allowed scientific exploration well beyond just real-time lattice curvature quantification.…”
Section: X-ray Beam Heatingmentioning
confidence: 99%
“…There is a drastic difference of the lattice curvature magnitude depending on the nature of said heat source, typically 0-20 • /μm for electron beam, 95 0-3 • /μm for laser, 30 and <0.1 • /μm for X-rays. 96 Although these experiments cannot be directly compared, the presence of lattice curvature is agnostic to the heat source and may be regarded effectively as a thermal effect. The reason for the dramatic differences in magnitudes is currently unknown but is expected to be a result of the corresponding temperature profiles induced by the specific radiation source.…”
Section: X-ray Beam Heatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, in general, plastic deformation occurs and defects arising from the density differences in epitaxy appear in complex and binary oxides, biomaterials, elemental semiconductors, and chalcogenides (4,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A further common result of the formation of defects during epitaxial growth low-symmetry nanoscale environments is the development of mesoscopic structural effects including a rotation of the crystal lattice (22,23,(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%